Advances in the Application of Cold Plasma Technology in Foods - Elisa Sainz-García; Fernando Alba-Elías (Foods, 2023)
In the last two decades, non-thermal processing technologies have gained widespread attention from the food industry, which is interested in mild and effective processes [...]